Peningkatan Kapasitas Siswa SMA Dalam Optimalisasi Lahan dan Mitigasi Dampak Perubahan Iklim - Prastyaningsih, Sri Rahayu; Hadinoto, Hadinoto; Sukma, Dodi; Yelmiza, Yelmiza; Nanda, Yoan De (P3M Politeknik Negeri Jember, 2024)
The Baitul Quran located in Pekanbaru, is relatively new, which means it has a lot of vacant land. As a result, tree planting is necessary to beautify the environment. Similarly, Pekanbaru Sports High School also has vacant land that needs to be utilized. The methods employed sosialization, planting practise, and evaluation. Sosialization is conducted to enhance the partners' knowledge about the role of trees in mitigating the effects of climate change. Tree planting and maintenance practices are implemented to ensure that partners are capable of planting and caring for trees, contributing to the reduction of global warming. The results at Ponpes Baitul Quran and Pekanbaru Sports High School indicate an increase in student knowledge about climate change. Although students at both schools have a similar understanding of climate change, students at Pekanbaru Sports High School demonstrate a stronger grasp of climate change. In contrast, students at Ponpes Baitul Quran show a better understanding of the practical aspects of planting and maintaining trees. Tree planting on the vacant land at these schools creates microclimate. The survival of the trees ranges from 95% to 99%. The best growth in durian trees, followed by eucalyptus, with areca nut trees showing the lowest.